Nonlinear boundary conditions for elliptic equations - Amster, P. (2005)
This work is devoted to the study of the elliptic equation Δu = f(x, u) in a bounded domain Ω ⊂ ℝ n with a nonlinear boundary condition. We obtain various existence results applying coincidence degree theory and the method of upper and lower solutions. © 2005 Texas State University - San Marcos.